Safety and Immunogenicity of Fully Liquid Hexavalent DTaP-IPV-HepB-Hib Vaccine in Healthy Infants in Russian Federation - L. S. Namazova-Baranova; S. M. Kharit; O. A. Perminova; V. V. Romanenko; I. V. Osipova; А. G. Asatryan; A. V. Goldstein; S. B'Chir; O. I. Lyabis (Эпидемиология и вакцинопрофилактика, 2019)
Relevance/aims: Multivalent vaccines are crucial in the control of diseases including diphtheria (D), tetanus (T), pertussis (P), polio, hepatitis B (HB), and Haemophilus influenzae type b (Hib [PRP~T]). To evaluate the safety and immunogenicity of a fully liquid, hexavalent DTaP-IPV-HB-PRP~Tvaccine in infants in the Russian Federation.Materials & methods. Infants (N=100) who had received a standalone HB vaccine within 24 hours after birth and at 1 month of age and a pentavalent (DTaP-IPV/PRP~T) vaccine at 3 and 4.5 months of age were enrolled and received the hexavalent DTaP-IPV-HB-PRP~T vaccine at 6 months of age. Safety was assessed from parental reports and immunogenicity using validated assays.Results. There were no safety concerns, with 38.0% and 49.0% of participants experiencing ≥ 1 solicited injection site and ≥ 1 solicited systemic reaction within 7 days after vaccination, respectively, and 16.0% reporting an unsolicited adverse event (AE) within 30 days after vaccination. The incidence of each solicited reaction with severity Grade 3 was ≤6.0% and all unsolicited AEs were Grade 1 or 2. Most AEs started ≤ 3 days post-vaccination, were short-lived, and resolved spontaneously. There were no serious AEs. On month post-vaccination 100.0% of participants had antibodies ≥ 10 mIU/ mL for anti-HBs, ≥ 0.01 IU/mL for anti-D and anti-T, ≥8 (1/dil) for anti-polio-1,2, 3, and 97.9% of participants had anti-PRP antibodies ≥ 0.15 gg/ml. For anti-PT and anti-FHA, GMCs were in the expected range.Conclusion. These results support vaccination with the DTaP-IPV-HB-PRP~T vaccine in the Russian Federation following the recommended national immunization schedule.